Respuesta :
Xsquared -5x= 2x-6
x^2 - 5x - 2x + 6 = 0
x^2 - 7x + 6 = 0
(x -6)(x-1) = 0
x-6 = 0, x = 6
x - 1 = 0, x = 1
answer
solutions
x = 1 and x =6
x^2 - 5x - 2x + 6 = 0
x^2 - 7x + 6 = 0
(x -6)(x-1) = 0
x-6 = 0, x = 6
x - 1 = 0, x = 1
answer
solutions
x = 1 and x =6
x^2 - 5x = 2x - 6
x^2 - 5x - 2x + 6 = 0
x^2 - 7x + 6 = 0
(x - 6)(x - 1) = 0
x - 6 = 0
x = 6
x - 1 = 0
x = 1
solutions are : x = 6 or x = 1
x^2 - 5x - 2x + 6 = 0
x^2 - 7x + 6 = 0
(x - 6)(x - 1) = 0
x - 6 = 0
x = 6
x - 1 = 0
x = 1
solutions are : x = 6 or x = 1